Assessment of rate and drivers of deforestation and forest degradation in the lower-tropical region: a case of Punarbas Municipality, Nepal - Subedi, Prajwol Babu; Ojha, Prakash; Mahara, Sandeep; Gautam, Deepak (Our Nature, 2022)
Deforestation and forest degradation (D and D), the most imminent threats to the survival of species and the viability of forests as a whole, is crucial to research its rate, as well as the underlying causes. The present study examined the rate and drivers that contribute to D and D in the Punarbas municipality of Kanchanpur district, Nepal. With the help of ArcGIS 10.8, an overall pattern and rate of D and D in the study area was identified using Land Satellite images from two different years (2000 AD and 2019 AD). 11 focus group discussions and 120 household surveys were carried out to collect data on key drivers of D and D. For data collection, stratified random sampling with a sampling intensity of 1% was used, and the Friedman test was applied for one-way repeated measures analysis of drivers by ranks. The study found that the annual rate of D and D of the study area from 2000 to 2019 AD was 0.63% and the major drivers were infrastructure development followed by illegal logging, agricultural expansion, livestock grazing forest fire, fuelwood collection, settlement/ resettlement, alien invasive species, and flood and landslide. Awareness programs are highly suggested to uplift the understanding level of local people, so they can act for themselves in the conservation of their local forest and ecosystem resources.